Narrowband Resting-State fNIRS Functional Connectivity in Autism Spectrum Disorder - Sun, Weiting; Wu, Xiaoyin; Zhang, Tingzhen; Lin, Fang; Sun, Huiwen; Li, Jun (Frontiers in Human Neuroscience, 2021)
Hemispherical asymmetry in the power spectrum of low-frequency spontaneous hemodynamic fluctuations has been previously observed in autism spectrum disorder (ASD). This observation may imply a specific narrow frequency band in which individuals with ASD could show more significant alteration in resting-state functional connectivity (RSFC). To test this assumption, we evaluated narrow-band RSFC at several frequencies for functional near-infrared spectroscopy (fNIRS) signals recorded from the bilateral temporal lobes on 25 children with ASD and 22 typically developing (TD) children. In several narrow frequency bands, we observed altered inter-hemispherical RSFC in ASD. However, in the band of 0.01-0.02 Hz, more mirrored channel pairs (or cortical sites) showed significantly weaker RSFC in ASD group. Receiver Operating Characteristic (ROC) analysis further demonstrated that RSFC in the narrow band of 0.01-0.02 Hz might have better differentiation ability between ASD and TD group. This may indicate the narrow-band RSFC could serve as a characteristic for the prediction of ASD.